2023
DOI: 10.1017/s095457942300113x
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to resilience and pathways to flourishing: Examining the added-value of multisystem research and intervention in contexts of war and forced displacement

Catherine Panter-Brick

Abstract: This paper examines the added-value that multisystem approaches bring to research and intervention in contexts of war and forced displacement. I highlight what is useful and truly innovative about systems-level work, aware that providing data-related evidence is only part of the story when connecting research to policy and practice. I discuss four types of added-value: these are conceptual, instrumental, capacity-building, and connectivity impacts that, respectively, aim to change current knowledge, improve im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In addition to supporting specific hypotheses about resilience, intervention research also has suggested that it is effective to combine multiple approaches, coordinated (stacked or aligned) to create synergy (Cicchetti, 2013;Hostinar & Miller, 2019;Masten, 2011Masten, , 2014Wyman et al, 2000;Yoshikawa, 1994). The humanitarian sector of international aid and development has played a leading role in demonstrating the power of coordinated multi-sector, multi-generational, and/or multilevel interventions for child well-being in populations of children at high risk due to extreme poverty, armed conflicts, famine, and natural disasters (Britto et al, 2017;Huebner et al, 2016;Panter-Brick, 2023;Richter et al, 2017). Synergistic effects of coordinated multi-sector and/or multilevel strategies are not surprising given early observations in the literature on risk and resilience that children in situations of high threat or deprivation often face multiple and accumulating risks (Rutter, 1979; see Masten et al, 1990).…”
Section: Shared Assumptions and Concepts Of Dp And Drsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to supporting specific hypotheses about resilience, intervention research also has suggested that it is effective to combine multiple approaches, coordinated (stacked or aligned) to create synergy (Cicchetti, 2013;Hostinar & Miller, 2019;Masten, 2011Masten, , 2014Wyman et al, 2000;Yoshikawa, 1994). The humanitarian sector of international aid and development has played a leading role in demonstrating the power of coordinated multi-sector, multi-generational, and/or multilevel interventions for child well-being in populations of children at high risk due to extreme poverty, armed conflicts, famine, and natural disasters (Britto et al, 2017;Huebner et al, 2016;Panter-Brick, 2023;Richter et al, 2017). Synergistic effects of coordinated multi-sector and/or multilevel strategies are not surprising given early observations in the literature on risk and resilience that children in situations of high threat or deprivation often face multiple and accumulating risks (Rutter, 1979; see Masten et al, 1990).…”
Section: Shared Assumptions and Concepts Of Dp And Drsmentioning
confidence: 99%
“…Research on the neurobiology of resilience blossomed when the tools for reliable assessments of processes within the human body became more feasible, including assessments of stress biology, gene methylation, immune function, and brain function (Feder et al, 2019;Feldman, 2021;Gunnar, 2020;Masten & Cicchetti, 2016;McEwen, 2020;McLaughlin et al, 2020;Shonkoff et al, 2021). Research focused on sociocultural processes, acculturation, discrimination, social justice, and historical trauma gained more attention (e.g., Jones et al, 2023;Marks et al, 2020;Murry et al, 2023;Panter-Brick, 2023;Spencer, 2023;Motti-Stefanidi, 2023;Suárez-Orozco et al, 2018;Wilbur & Gone, 2023). Multisystem measures of protective factors became prominent, such as the Child and Youth Resilience Measure (Ungar & Liebenberg, 2011) and indices of positive (rather than adverse) childhood experiences, such as the Benevolent Childhood Experiences scale (Narayan et al, 2023).…”
Section: Shared Assumptions and Concepts Of Dp And Drsmentioning
confidence: 99%
“…As Bennett (2018) has argued, we live in a time when alternative forms of humanitarian action need to be “re-imagined.” The protracted form of humanitarian crises, including the global refugee crisis, has called for a “rethink” and a “modernization” of international models of humanitarian assistance, in ways that put actual “people” squarely at the center of humanitarian action ( Bennett, 2018 ). For example, new models of humanitarian assistance are questioning the underlying assumptions of power and governance in the classical, largely hierarchical, approach to working with people in need, known as “crisis humanitarianism” ( Currion, 2018 ; Hilhorst, 2018 ; Panter-Brick, 2023 ). A network approach, for example, encourages thinking about systems, and transforming systems, rather than responding to individual need.…”
Section: Introductionmentioning
confidence: 99%